Smart Cities and U-space. Preparing for UAV operations in urban airspace - Stelmach-Fita, Beata (Bulletin of Geography. Socio-economic Series, 2025)
This article presents the 4D Urban Area Model for Unmanned Aerial Vehicle (UAV) Risk Assessment – a framework designed to support the safe integration of drones in low-altitude urban airspace. The model builds on interoperable 3D city models, is in line with the Specific Operations Risk Assessment (SORA) methodology and U-space regulations, and introduces a fourth dimension: time. Through a nationwide survey of Polish municipalities and consultations with Polish Air Navigation Services Agency (PANSA) experts, the author identified population density and mobility data as essential for assessing drone-related risks. As a result, a 12-interval daily temporal layer was proposed to support dynamic risk zoning – initially with historical data on traffic density and ultimately, in the future, with real-time updates of this data and other obstacles via digital twins. ...